IMPLEMENTATION OF ADVANCE CARE PLANNING (ACP) IN GENERAL PRACTICE THROUGH THE PROVISION OF OUTREACH ACP FACILITATORS. Issue 2 (1st June 2013) - Mann, J; Milner, R
Abstract : Background: Following the success of the smaller 2010 pilot study, this initiative was 12 month collaboration between Barwon Health's Respecting Patient Choices (RPC) program, 18 General Practice Clinics from within the Barwon region and the Barwon Medicare Local. Aim: To engage with General Practitioners in providing advance care planning (ACP) to their patients demonstrating a sustainable ACP model for general practice. Methods: Funding provided by Barwon Health for 2.0 EFT ACP Facilitator positions. Key stakeholders were engaged and Memorandum of Understanding developed. Participating practices were identified through an expression of interest and GPs were encouraged to complete their own ACP. Patients with chronic or life limiting illness and aged were the target population including other interested individuals. This was achieved via the >75 Health Assessment, Chronic Disease Management Planning and routine consultations. Engagement with GP staff occurred collaboratively with Barwon Medicare Local throughout the project period. Results: Providing trained staff from a funded ACP program to 18 practices in the Geelong region has resulted in 1350 referrals for ACP and a completion rate of 87% (1174). From this cohort, there have been 295 in-patient episodes of care with a number of ACP's implemented as required. Discussion: Similar findings to the smaller 2010 pilot study have been demonstrated through patients exhibiting a high rate of acceptance, participation, document completion and satisfaction when ACP is provided through GP's. Conclusion: This larger study has demonstrated that General Practice is integral to the commencement of ACP discussions in the community, where there is established trust and confidence and whilst patients are 'relatively well', in the absence of acute illnesses. Barwon Health's catchment includes a higher proportion of older persons in comparison to the state average and is therefore significant that the general awareness of ACP is raised routinely within the community.